Threat of an influenza pandemic: family physicians in the front line - Opstelten, Wim (BioMed Central, 2009)
BACKGROUND: The chance of an influenza pandemic is real and clinicians should keep themselves informed about the rationale and science behind preventive and therapeutic principles relating to an (impending) influenza pandemic. DISCUSSION: Vaccination is considered the best prevention in case of a pandemic threat and first choice to contain the impact of a pandemic. Pending the availability of an effective pandemic vaccine, antivirals are likely the only effective agents for prevention and treatment. When an influenza pandemic is impending, all interventions aim to prevent people becoming infected and to suppress replication and transmission of the virus as much as possible. Antivirals will be prescribed to patients with laboratory confirmed pre-pandemic influenza as well as to their contacts (post-exposure prophylaxis) which may delay development of or even prevent a pandemic. During a manifest influenza pandemic, however, there is large-scale spreading of the influenza virus. Therefore, preventive use of antivirals is less efficient to prevent transmission. Delaying the pandemic is then important in order to prevent exhausting public health resources and disruption of society. Thus, during a manifest pandemic everyone with influenza symptoms should receive antivirals as quickly as possible, regardless of virological confirmation. To ensure optimal effectiveness of antivirals and to minimize development of drug resistant viral strains, the use of antivirals for annual influenza should be restrictive. The crucial position of family physicians during an (impending) influenza pandemic necessitates the development of primary health care guidelines on this topic for all countries. SUMMARY: Family physicians will play a key role in assessing and treating victims of a new influenza virus, and in reassuring the worried well. We outline various possible interventions in the event of an impending and a manifest influenza pandemic, such as non-medial measures, prescription of antivirals, and vaccination, and emphasize the need for pandemic influenza preparedness.